COOK FOOD AND BEVERAGE PRODUCT PERFORMANCE IN IMPROVING THE ZURI DUMAI HOTEL OPERATIONS - Khoyrika Makharoni Makharoni; Mariaty Ibrahim Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Performance for the corporate world is a phenomenon of the success or failure of predetermined corporate goals. Leaders or managers often don't pay much attention to employee performance except after bad conditions or events or things that are problematic. Often leaders do not know that employee performance has declined so that companies are facing a very serious crisis. This study aims to find out how Cook's employees perform in improving the operations of The Zuri Dumai Hotel. In order for employee performance to run well, several indicators must be carried out in the form of work quality, work quantity, responsibility, cooperation and initiative. This study uses qualitative research methods and to obtain the necessary data, the authors use interview, observation and documentation techniques. From the results of the author's research for 4 months at The Zuri Dumai Hotel, it was found that the performance of cook employees at The Zuri Dumai Hotel was quite good, but there were several procedures that had not gone well. Keywords: Employee Performance, Performance Indicators, The Zuri Hotel Dumai